An old disease on the rise: new approaches to syphilis in pregnancy. Issue 2 (April 2021) - Liew, Zi-Qi; Ly, Victoria; Olson-Chen, Courtney
Abstract : Purpose of review: Maternal and congenital syphilis infection is on the rise in the United States and worldwide. Without adequate testing or provider recognition of infection, treatment can be neglected resulting in significant perinatal morbidity and mortality. This review article discusses the epidemiology of T. pallidum, describes novel diagnostic tests, and considers the need to expand therapeutic options. Recent findings: A new chemiluminescence immunoassay for use in the reverse-sequence algorithm is more sensitive and specific in pregnant women than previously noted and is helpful for identifying pregnant women at highest risk for neonatal congenital syphilis. Point-of-care testing may be used to detect early syphilitic disease and provide same-day testing and treatment. Randomized control trials of oral cefixime for treatment of syphilis are paving the way for potential use in pregnant women. Penicillin skin testing, challenge, and desensitization in pregnancy can be done safely. Summary: Congenital syphilis is a preventable disease and treatable infection in the modern world, but we are still met with challenges in its eradication. We should proceed with advancing efficient laboratory testing, expanding medical therapy, and implementing public health measures to curb the rise of the disease.